Force Aware Haptic Rendering for Intubation Simulation - Meng, Yan; ., . (International Journal of Engineering and Technology, 2018)
We introduce a new haptic rendering method for neonatal endotracheal intubation simulation. The challenging procedure involves multiple models of different material properties, and is performed in the narrow oral cavity involving multiple contacts with tongue, lips, and laryngoscope. Our method first sets up simple collision detection mechanism with adaptive inner sphere tree structure for deformable tongue tissue. Then a collision response is handled with a novel force aware projective position correction. Our method is proved to be effective for heterogeneous simulation environment, therefore can be applied to surgical simulation with similar difficult settings.Â Â Â